Writing in Spanish as a heritage language: A multidimensional analysis. (11th December 2020) - Asención‐Delaney, Yuly
Abstract: Spanish heritage speakers in the United States exhibit a wide range of linguistic profiles due to a combination of political, social, and educational factors. Most of them acquire Spanish at home without formal instruction in writing. Although previous research has explored the main challenges faced by these learners in Spanish writing courses, no current research has examined the linguistic features that characterize their writing using a corpus‐based approach that would facilitate the identification of their actual patterns of language use. This study presents the findings of a multidimensional analysis of the writing produced by Spanish heritage learners in three composition classes at the college level. The findings show how 47 lexical and grammatical features co‐occur in four distinctive discourse types: informational, descriptive, narrative, and detached, with some variation observed across proficiency levels. The Challenge: Understanding Spanish heritage learners' (SHLs') writing is critical to better meet this population's educational needs in college Spanish courses. As teachers, we would like to know how students' lexico‐grammatical associations in writing help us identify their academic discourse abilities development in the heritage language. This study explores this question through a multidimensional analysis of a corpus of academic texts written by Spanish heritage learners at different levels of proficiency.